Promotion path of digital transformation in China’s manufacturing industry based on technology-organisation-environment framework - Xu, Ke (Journal of Business Economics and Management, 2025)
As the global economy becomes increasingly digitalised, the digital transformation of manufacturing has become an important way to enhance national competitiveness and corporate viability. This study focuses on the digital transformation of the manufacturing industry. First, the digital transformation of listed manufacturing companies is scientifically measured and their current state of transformation analysed. Then, the technology-organisation-environment framework is used to examine the driving factors of digital transformation. Based on this, fuzzy-set qualitative comparative analysis is employed to summarise different digital transformation configurations. The findings show that the digital transformation of China’s manufacturing industry is still in its early stages, with significant regional differences. Achieving a high level of digital transformation can be accomplished through four paths: environment- dependent, strategic leadership, internally capability support, and comprehensive-driven approaches. Finally, practical guidance is provided on accelerating the digital transformation process and promoting high-quality development in the manufacturing industry.